Adaptive Sports Exposure Impacts Pediatric Orthopaedic Surgeon Comfort in Treating Patients With Disabilities - Charlotte F. Wahle, BA; Nora A. Galoustian, BA; Nicole J. Newman-Hung, MD; Alexander Rueda, MPH; Christina Im, BA; Eghosa Edogun, MD; Charlotte Poplawski, MD; Sharon L. Hame, MD; Rachel M. Thompson, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: Pediatric patients with physical disabilities often have difficulty accessing providers who are comfortable treating this unique patient population. The purpose of the study is to identify factors associated with increased pediatric orthopaedic surgeon familiarity in treating patients with disabilities and to assess whether involvement with adaptive sports (AS) improves their comfort level in treating these patients. Methods: An anonymous 36-question survey was administered from May to June 2024 to members of the Pediatric Orthopaedic Society of North America (POSNA). Demographic information and clinical practice details were collected. Survey questions assessed the comfort level of pediatric orthopaedic surgeons with treating and counseling patients with various types of disabilities, as well as their familiarity with AS. Data analysis was performed using chi-squared analysis, fisher exact test, and the Mann-Whitney U. Results: A total of 190 responses were recorded (13% of POSNA membership). Participants' ages ranged from 32 to 90; 93% of respondents completed fellowship training in pediatric orthopaedic surgery. Surgeon experience ranged from <5 to >20 years in practice. Surgeons with more experience had significantly higher comfort levels in treating patients with physical disabilities and counseling them regarding sports participation (P < .01, P < .001, respectively). Surgeons who treat a higher proportion of patients with physical disabilities were also significantly more likely to have attended an AS event (P = .02). Furthermore, there was a statistically significant association between AS event attendance and comfort counseling patients with physical disabilities on sports risks (P < .001). Conclusions: Pediatric orthopaedic surgeons with more practice experience and with greater exposure to patients with disabilities are more comfortable in treating and counseling these patients with disabilities. However, the data suggests that attending an AS event may improve pediatric orthopaedic surgeons’ comfort and confidence in treating patients with disabilities regardless of practice experience. While AS have well-documented benefits for participants–including participation, community, and health benefits–these events may also provide an excellent opportunity for exposing pediatric orthopaedic surgeons to patients with disabilities early in their career, with significant impact on their ability to treat patients with disabilities. Key Concepts: (1) Pediatric orthopaedic surgeons with more years in practice report significantly greater comfort treating and counseling patients with disabilities. (2) Surgeons who have attended adaptive sports (AS) events demonstrate significantly higher comfort levels in caring for patients with disabilities, regardless of years in practice. (3) Many physicians lack formal training and experience caring for individuals with disabilities, highlighting the need for improved disability education in medical training. (4) Incorporating AS exposure into early medical education may help address healthcare disparities and build a more inclusive physician workforce. Level of Evidence: Level II Prospective Survey.